Tactics Against Antiquity: Contemporary Ancient Messene - Koutsomichalis, Marinos (My University, 2026)
Live performance of the hybrid artwork 'Tactics against Antiquity: the contemporary ancient Messene' at the Tuned City Festival. 'Tactics against Antiquity' probes the making and unmaking of intra-personal and extra-personal place-hood, history, and memory. Inspired by the ancient practice of ‘peripatos’ – both as a political act and as a strategy for epistemic inquiry – the artist leads a walk through the ruins of ancient Messene, presenting the audience with audio documents of, and with creative responses to, his own personal (un)makings at play. Tactics against Antiquity draw on found audio, folk traditions, abstract sound synthesis, dark ecology, politicised narratives, transgressive audioscape juxtapositions, tactical silence, speculative ethnography, and real time exploration of various acoustic, electromagnetic, and geophysical phenomena in-situ, in this way intending to bring forth a post-historical and meta-phenomenological perspective of the ‘contemporary’ ancient Messene. http://www.tunedcity.net/?page_id=5478